Abnormal B cell glycosylation in autoimmunity: A new potential treatment strategy - Morel, Marie; Pochard, Pierre; Echchih, Wiam; Dueymes, Maryvonne; Bagacean, Cristina; Jousse-Joulin, Sandrine; Devauchelle-Pensec, Valérie; Cornec, Divi; Jamin, Christophe; Pers, Jacques-Olivier; Bordron, Anne (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) and primary Sjögren’s syndrome (pSS) are two autoimmune diseases characterised by the production of pathogenic autoreactive antibodies. Their aetiology is poorly understood. Nevertheless, they have been shown to involve several factors, such as infections and epigenetic mechanisms. They also likely involve a physiological process known as glycosylation. Both SLE T cell markers and pSS-associated autoantibodies exhibit abnormal glycosylation. Such dysregulation suggests that defective glycosylation may also occur in B cells, thereby modifying their behaviour and reactivity. This study aimed to investigate B cell subset glycosylation in SLE, pSS and healthy donors and to extend the glycan profile to serum proteins and immunoglobulins. We used optimised lectin-based tests to demonstrate specific glycosylation profiles on B cell subsets that were specifically altered in both diseases. Compared to the healthy donor B cells, the SLE B cells exhibited hypofucosylation, whereas only the pSS B cells exhibited hyposialylation. Additionally, the SLE B lymphocytes had more galactose linked to N-acetylglucosamine or N-acetylgalactosamine (Gal-GlcNAc/Gal-GalNAc) residues on their cell surface markers. Interestingly, some similar alterations were observed in serum proteins, including immunoglobulins. These findings indicate that any perturbation of the natural glycosylation process in B cells could result in the development of pathogenic autoantibodies. The B cell glycoprofile can be established as a preferred biomarker for characterising pathologies and adapted therapeutics can be used for patients if there is a correlation between the extent of these alterations and the severity of the autoimmune diseases.